Ion transport, sensing applications, and redox gradient formation: an electrochemical study of electronically conducting polymers - Salzer, Corey A., author; Elliott, C. Michael, advisor (Colorado State University. Libraries, 2002)
Conducting polymers are a unique class of materials that exhibit very interesting electronic characteristics. The ease of modification of the polymers and their physical and electronic properties make these very attractive materials for a large number of applications. Conducting polymers have been studied for use in light emitting devices, as sensing materials, for drug delivery, and antistatic coatings. Fundamental to most of the polymers potential applications is the occurrence of ion transport in and out of the polymer material during oxidation and reduction processes.

In Chapter Two, a rotating ring-disk electrochemical method is applied to the study of ion transport in films of poly(pyrrole). Many researchers have examined the nature of ion flux in conducting polymers, but the methods they employed have drawbacks to the quantitative, in situ measurement of the ion transport occurring in the polymers. We present a means of surmounting the shortcomings of the other methods of analyzing ion transport in conducting polymers and give insight into the nature of ion flux in poly(pyrrole) films.

Chapters Three and Four report on the use of poly(3,4-diphenylpyrrole) films as a sensing material for chlorinated hydrocarbons. Chapter Three employs impedance spectroscopy as a tool to monitor capacitance and resistance changes of the polymer that occurs upon interaction of the film with dichloromethane in an aqueous environment. These impedance changes were used to sense the presence of dichloromethane. Chapter Four uses the di-substituted polymer films as the sensing material in a vapor sensor possessing selectivity for small, chlorinated hydrocarbons. Here, changes in film resistance occur as a result of a charge transfer complex between the polymer and the analyte vapor. The direction and magnitude of the resistance change is used to identify the vapor.

In Chapter Five, chemically locked redox gradients are formed in ruthenium- and iron-based redox polymers. Thermally polymerizable anions were incorporated into the polymers for polymerization with pendant acrylate groups on the redox polymer. The intent was to permanently lock the redox gradients in the film; thus improving upon the on the thermally locked gradients formed in similar films by other researchers.
Keywords: analytical chemistry; polymers; polymer chemistry